Lagos state digest of statistics, 1976 - Lagos State Government; Sanwo, Patrick (Lagos: Lagos State Ministry of Economic Development and Establishments, 1976)
In this edition the data has been generally brought up to date with the inclusion of figures for more recent years. In addition an entirely new section on water supply has been added.
rpm 21/02/2018
Loans
Keywords: Statistics; Digest of statistics; Lagos